Experimental Validation of a Methodology for Determining Soil pH and Specific Electrical Conductance in Samples of Geological and Soil Evidence in Forensic Environmental Investigations in the Absence of Standard Samples - Galina I. Bebeshko; Georgii G. Omel'yanyuk; Marina V. Nikulina; Alsu R. Valitova (Теория и практика судебной экспертизы, 2017)
The paper describes an experiment in validation of a forensic methodology for determining the hydrogen potential (pH) and specific conductance (SC) in samples of geological and soil evidence for the purposes of forensic environmental investigation. Validation was aimed at standardizing the conditions of aqueous extract preparation, since the conditions prescribed by corresponding regulations varied significantly. Given the absence of adequate standard samples at the time of the experiment, control samples had to be selected, and reference values of pH and SC in these control samples had to be determined through average values of the overall set of measurements. The experiment consisted of 5 operators independently conducting six parallel analyses of three control samples, each operator working at a different time and using their own assay kits. Both pH and SC values were measured in two different dilutions, each after 5 minutes, 1 hour, and 24 hours of holding time. Statistical calculations of the obtained set of results yielded reference values for target parameters in three control samples for different aqueous extract preparation conditions. It was demonstrated that when the extract is diluted to 1 : 2.5 soil/water ratio, measurements are on average 1.8 times higher for SC, and 0.20 pts lower for pH, compared to 1 : 5 soil/water dilution. Since 1 : 5 is the standard dilution for aqueous extracts, 1 : 2.5 dilutions call for a corresponding adjustment. Acceptable holding time between dilution and measurement has been established to vary between 5 minutes and 1 hour. When re-validated a year later, the obtained mean values of pH and SC in three control samples of soil fit within the uncertainty interval for adopted reference values.The outcomes demonstrate the stability of control sample properties and reliability of the applied methodology.